The Role of an Integrative Approach in Developing Critical Thinking Skills in Primary School Students - Zokirova Masuma Qahramonjon qizi (Indonesian Journal Publisher, 2025)
This study aims to examine the role of an integrative approach in developing critical thinking skills among primary school students through the combination of interdisciplinary teaching methods, active learning, and psychological development strategies. Employing a qualitative and descriptive research design, the study explores how integrative pedagogy supports independent reasoning, creativity, and reflective judgment in young learners. Data were analyzed from pedagogical literature, classroom observations, and theoretical models of cognitive development. The results indicate that integrating multiple disciplines—such as science, mathematics, and language—enhances students’ ability to analyze, evaluate, and apply information in real-life contexts. Furthermore, psychological engagement through problem-based and collaborative learning encourages curiosity, motivation, and metacognitive awareness. The research concludes that the integrative approach effectively cultivates both intellectual and moral development, preparing primary students to become analytical, responsible, and adaptive individuals capable of navigating 21st-century challenges.